The Utilization of Video-Based Learning Resources and Self-regulated learning on the Medical Skills of Health Vocational School Students - Arvandi Arvandi; Sofyan Sofyan; Akhmad Habibi (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2026)
Background: Medical kinesthetic skills are an essential competency in Vocational High School (SMK) education in the health sector that requires precise procedural mastery, so effective learning innovations are needed through the use of video-based learning resources supported by self-regulated learning behavior.Aims: This study aims to analyze the effect of the use of learning videos and self-regulated learning on the medical kinesthetic skills of vocational school students in the health sector.Methods: This study used a quantitative approach with a cross-cut explanatory design involving 200 students of SMK Fania Salsabila Jambi City. Data analysis was carried out using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) to test the direct and indirect relationships between variables.Results: The results showed that the use of video learning had a significant positive effect on self-regulated learning (β = 0.728; f² = 1.128), and self-regulated learning had a strong effect on medical kinesthetic skills (β = 0.655; f² = 0.598). However, the direct influence of video on kinesthetic skills was relatively small (β = 0.201; f² = 0.056), suggesting that self-regulated learning plays a key mediating role.Conclusion: These findings reinforce the Cognitive Theory of Multimedia Learning that the effectiveness of video depends on the active involvement of students. Thus, the integration of instructional video design and independent learning strategies is key in optimizing the learning of procedural skills in vocational schools in the health sector.